2013
DOI: 10.1111/clr.12124
|View full text |Cite
|
Sign up to set email alerts
|

The influence of prophylactic antibiotic administration on post‐operative morbidity in dental implant surgery. A prospective double blind randomized controlled clinical trial

Abstract: The use of for dental implant surgery may be justified, as it appears to improve implant survival in the short term and also results in less post-operative pain and interference with daily activities. From the results of this study, it appears that prophylactic antibiotics may also be beneficial both in terms of implant survival, especially when the surgical procedure is prolonged due to its difficulty, high number of implants placed or operator's inexperience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
131
0
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(141 citation statements)
references
References 19 publications
1
131
0
8
Order By: Relevance
“…Although multiple recent RCTs (10,11,12) have provided evidence that use of pre-operative antibiotics may reduce implant failures, only 51.6% of the 217 respondents to our survey indicated that they use antibiotics pre-operatively prior to dental implant placement. However, as previously noted, a similar number of studies (6,7,8,9) have failed to provide appropriate scientific evidence to recommend or discourage the use of prophylactic antibiotics to prevent complications and failure of dental implants.…”
Section: Discussionmentioning
confidence: 66%
“…Although multiple recent RCTs (10,11,12) have provided evidence that use of pre-operative antibiotics may reduce implant failures, only 51.6% of the 217 respondents to our survey indicated that they use antibiotics pre-operatively prior to dental implant placement. However, as previously noted, a similar number of studies (6,7,8,9) have failed to provide appropriate scientific evidence to recommend or discourage the use of prophylactic antibiotics to prevent complications and failure of dental implants.…”
Section: Discussionmentioning
confidence: 66%
“…Preoperative and postoperative systemic antibiotic treatment has been advocated vigorously, but the effectiveness of the drugs is unclear 19 . Recently, it has been reported that systemic drugs in implant surgery are helpful for reducing complications and postoperative infection 1 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…Flapless dental implant surgery has become a popular technique to minimize surgical injury and post‐surgical reactions. However, post‐surgical wound healing is not always predictable because of the lack of information about evidence‐based postoperative care protocols 1 . Some studies showed positive benefits of the routine use of prophylactic antibiotics in early soft tissue healing after surgery, 1–3 whereas other studies showed no significant effects 4–6 …”
mentioning
confidence: 99%
“…This suggests that the bi-functional coating (Ca-P+MNZ+SIM) prepared in this study could maintain its antibacterial capability for a certain period of time in a liquid environment similar to in vivo conditions. The initial post-operative stage is a dangerous stage for patients receiving orthopedic implants, due to the increased risk of infection caused by pathogenic microorganisms, and prophylactic antibiotic application is a simple and practical way to circumvent this problem [26][29]. The systemic application of antibiotics has several drawbacks as outlined above, which can be averted by the local release of MNZ from the bi-functional coating over several days.…”
Section: Discussionmentioning
confidence: 99%